PHYSICAL HEALTH STATUS OF PEOPLE AGED 60 YEARS AND OVER AT NURSING CLUBS IN DISTRICT 10, HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2021)
Background: The age of support and endurance against external and internal factors and agents is greatly less so that the need for health care including physical and mental training to improve the quality of life is essential especially the physical health of the elderly.Target:. Determination of physical health scores and associations of people aged 60 years and older at nursing clubs in District 10, Ho Chi Minh City, in 2019.Methods and materials: Descriptive cross-section study. People aged 60 years and over who have been training at nursing clubs living in District 10, Ho Chi Minh City were surveyed from September 2018 to October 2019.Results: The study showed an average score of 63.3 in ±17.3 points. In particular, physical activity: 61.0±23.1; physical limitations: 57.2±26.1; pain sensation: 68.2±22,2; general health: 59.6±14.9. Considering the relationship, as the age group increases, the mean score of the elderly's quality of life decreases statistically significantly in four áreas (p
Keywords: Physical health, the elderly, Ho Chi Minh City